2019
DOI: 10.1097/adm.0000000000000503
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Physician Perspectives on Treating Tobacco Dependence in Hospitalized Smokers With Substance Use Disorders: A Mixed Methods Study

Abstract: Objective: Individuals with substance use disorders have a high prevalence of smoking cigarettes. Hospitalization represents an opportunity to deliver concurrent treatment for tobacco and other substances. Using a sequential explanatory mixed methods design, we characterized practices and perspectives of patients and physicians about smoking cessation counseling during inpatient addiction medicine consultations. Methods: We abstracted data from 694 consecutive inpatient addiction consult notes to quantify how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Further, experiences of stigma or poor health literacy may contribute to AMA discharges [11]. Additional strategies to mitigate this outcome include expanding trauma-informed care, linkages, and follow-up with culturally and linguistically competent peers, in-hospital harm reduction services, and treatment of nicotine withdrawal [10,11,30,32,33]. Hospital-based harm reduction including syringe distribution and supervised injection were acceptable to hospitalized patients who inject drugs, but it is not yet known if these approaches improve outcomes, including AMA discharge [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Further, experiences of stigma or poor health literacy may contribute to AMA discharges [11]. Additional strategies to mitigate this outcome include expanding trauma-informed care, linkages, and follow-up with culturally and linguistically competent peers, in-hospital harm reduction services, and treatment of nicotine withdrawal [10,11,30,32,33]. Hospital-based harm reduction including syringe distribution and supervised injection were acceptable to hospitalized patients who inject drugs, but it is not yet known if these approaches improve outcomes, including AMA discharge [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, more than half of the health professionals and workers identified that most adult smokers are interested in quitting, and that brief advice from healthcare professionals is a viable method to increase the likelihood of quitting successfully. Despite knowing that brief interventions are effective, the practice of delivering interventions was low, as has been shown in the literature [21][22][23] ; more than half of this sample did not respond to, or skipped, questions regarding the 5As, perhaps indicating either a lack of general knowledge about the 5As or a lack of implementation of the 5As. Even among those who responded, only 58% reported assisting patients with quit attempts and less than a quarter endorsed arranging follow-up.…”
Section: Discussionmentioning
confidence: 80%
“…Reports with multiple ACS sites [21][22][23][24][25] Boston Medical Center [26][27][28][29][30][31] Massachusetts General Hospital 14,[32][33][34][35] New York City Hospital + Health Systems 36 Oregon Health & Science University 7,8,10,11,12,13,15,[37][38][39][40][41][42] Rush (Chicago) SUIT [43][44][45] University of California San Francisco 46 University of Colorado 47 University of Maryland [48][49][50] Yale University 51 Unspecified site 52,53 Allegheny Health Network 54 ✓…”
Section: Psychiatry Consult Liaison Servicementioning
confidence: 99%